73304-23-4153-6-96-8 - Ott, Thomas 1966 June 10- (Fantagraphics, 2008)
When clearing up the cell of a prisoner who has been sentenced to death and subsequently executed, a prison guard finds a small piece of paper with a combination of numbers on it. On the spur of the moment, he puts it into his pocket. As the guard lives a solitary, monotonous life, the numbers on the paper awake his curiosity. To find out their hidden meaning could add a new meaning to his life as well, so the guard stumbles into situations in which the number or part of it seem to achieve a certain importance and offer him hints and possible solutions. And the numbers signal a radical change in his luck. He gets to know a woman, falls in love with her, and one night, in a casino, he wins a huge amount of money when gambling on these numbers. But the next morning, the woman and money have disappeared. The man goes in search of the woman and the money. But from that day on, his luck changes and the numbers bring him only bad luck, sending him inexorably into an abyss that he might not recover from" -- from publisher's web site.